The Effect of Eight Weeks Resistance and Endurance training on Some Angiogenesis factors of Hippocampus Tissue in male Wistar rats - Mojtaba Sadegh Ghomi; Majid Kashef; Mojtaba Salehpour (Shahid Beheshti University, 2021)
Purpose: One of the cause of adaptations due to exercise training is increased capillary density or angiogenesis. increased blood flow to hippocampus tissue causes improvement of memory, learning and neurogenesis process and prevention from accession brain disease like Alzheimer. The Aim of this study was to compare the effect of Eight weeks resistance and Endurance running on VEGF-A and FGF-2 levels of hippocampus tissue in male Wistar rats.Methods: This study in aim perspective was developmental and in method perspective was Experimental. For this aim 32 male Wistar rats, divided randomly in four groups (Resistance Training, Running, Sham and control) and training groups exercised for eight weeks. For evaluation of VEGF-A and FGF-2 concentrations of hippocampus tissue used from sandwich Elisa method and for hypothesizes test from one-way ANOVA and Tukey post hoc used.Results: Results show that Eight weeks' resistance and endurance training Respectively cause significant increase in VEGF-A (P = 0.000), (P = 0.000) and FGF-2 (P = 0.000), (P = 0.000) than to control group. Also there are significant different in concentrations of VEGF-A (P = 0.000) and FGF-2 (P = 0.000) of hippocampus tissue between resistance and endurance running groups. In addition, no significant differences was observed in VEGF-A (P = 0.982) and FGF-2 (P = 1.000) indexes between exercise sham and control groups.Conclusion: Results of this study show that eight weeks' resistance training cause more significant increase on effective angiogenic factors in hippocampus tissue of male Wistar rats than endurance running training group.